Nicaragua : Fifth and Sixth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver and Modification of Performance Criteria, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2004)
This paper focuses on Nicaragua's Fifth and Sixth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver and Modification of Performance Criteria. The macroeconomic performance has been broadly satisfactory. Economic growth is accelerating; inflation, albeit somewhat higher owing to increased oil prices, remains under control; and official reserves are above program targets. The performance criterion on public savings and all indicative fiscal targets were missed in late 2003, but the March 2004 targets were met and measures have been taken to keep the program on track.